Ureterocolic fistula detected by mercaptoacetyltriglycine (MAG-3) diuretic renography including single photon emission CT and low-dose CT (SPECT–CT). Issue 9 (30th September 2019) - Draaisma, Jos; Janssen, Marcel; Graafland, Niels; Stommel, Martijn
Abstract : We describe the case of a 60‐year‐old man with a ureterocolic fistula following laparoscopic sigmoid resection. The fistulous tract between the left ureter and sigmoid colon was detected by mercaptoacetyltriglycine diuretic renography including single photon emission CT with low-dose CT. Ureteroneocystostomy was successfully performed.